Hubungan Safety Talk dan Safety Patrol Terhadap Produktivitas Karyawan Pada PT. Krakatau Argo Logistics - Udi Iswadi; Masitoh (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2021)
Productivity is an effort to improve the quality of work life, believing today is better than tomorrow. To be able to make it happen, the employee's safety and safety to avoid work accidents need to be prioritized through quiet talk of safety or known as safety talk to harmonize and maintain it. It is necessary to be accompanied by security supervision which can be called a safety patrol of PT. Krakatau Argo Logistics. This study aims to determine the effect of safety talk and safety patrol for employees on employee productivity. The method used in this study is a quantitative method and can be interpreted as a research method based on the positivism philosophy, used to examine populations and specific samples with data collection techniques, through questionnaire distribution, the number of samples as many as 68 employees in PT. Krakatau Argo Logistics, taken by simple random random technique. The results of this study indicate the results that the variable safety talk and safety patrol (X) on employee productivity (Y) F count is 190,277 and the F table value is 3.14. This shows that F count> F table (190,277> 3.14) with a significance level of (0,000 <0.05) Thus it can be concluded that safety talk and safety patrol have a significant effect on employee productivity.